The adoption of contact tracing applications of COVID-19 by European governments. Issue 1 (2nd January 2021) - Jacob, Steve; Lawarée, Justin
Abstract: Contact tracing can be defined as the identification and the monitoring of each person who has been in contact with an infected person. However, the effectiveness of manual contact tracing is hindered by low responsiveness, limited data processing, respondent omissions or the inability to identify individuals in a crowd. Faced with these limitations, research on digital contact tracing has been carried out. Digital contact tracing, especially smartphone contact tracing apps, has progressively appeared as a solution to slow the spread of the SARS-CoV-2 pandemic. Such a technological solution allows to track, in real-time, a massive number of (potentially) infected individuals within a given population. Despite high acceptability rates among the population and positive evaluations regarding its effectiveness, the implementation of these digital tracing applications has raised many technological and political questions. By conducting a thematic analysis, this research identifies the technological and policy issues with regard to digital tracing in three European countries.